20 years of BioMalPar: building a collaborative malaria research network - Frischknecht, Friedrich; Rayner, Julian C.; Waters, Andrew P. (Trends in parasitology, 2024)
In 2004 the first annual BioMalPar meeting was held at EMBL Heidelberg, bringing together researchers from around the world with the goal of building connections between malaria research groups in Europe. Twenty years on it is time to reflect on what was achieved and to look ahead to the future.